Green Route Synthesis of Amorphous Silica from Oil Palm Decanter Cake: From Literature Review to Experiments - Nursyahirah Abdul Rahim; Noorfidza Yub Harun; Anwar Ameen Hezam Saeed; Muhammad Roil Bilad (Universitas Pendidikan Indonesia, 2023)
Numerous agricultural wastes are well-defined as low-cost sources and rich in silica content. The residue of oil palm wastes combustion seems a promising silica source and can be recovered through a straightforward method. In this study, the combustion followed by an alkaline extraction method was employed to extract high purity of silica. The oven-dried oil palm decanter cake (DOPDC) was heated at combustion temperatures of 600, 700, 800, and 900°C to produce OPDC ashes (OPDCA), followed by an alkaline extraction using 5M of NaOH solution. Thermogravimetric analysis (TGA) was used to observe the thermal behavior of DOPDC where the suitable combustion temperatures to produce silica ranged between 600 and 1000 ℃. X-Ray Fluorescence (XRF) analysis showed that silica contents were 31-36% after combustion, increasing to 76.95% after the chemical treatment. Moreover, the spherical shape of the silica was observed through electron microscope analysis. It was represented by the aggregation of silica after going through chemical treatment. The X-Ray Diffraction analysis also proved that the amorphous silica was produced, characterized by the hump-shaped spectrum. The infrared analysis confirmed that the silica had been successfully extracted from OPDCA by the presence of silica functional groups shown in the spectrum.